Steam oxidation of advanced high temperature resistant alloys for ultra-supercritical applications - Lukaszewicz, Mikolaj (Cranfield University, 2012)
Steam oxidation of heat exchanger tubing is of growing interest as increasing the efficiencies of conventional pulverised fuel fired power plants requires higher steam temperatures and pressures. These new, more severe steam conditions result in faster steam oxidation reactions, which can significantly reduce the lifetime of boiler components. This thesis reports results from an investigation of the steam oxidation of the high temperature resistant alloys. It covers an analysis of the impact of temperature, steam flow rate, specimen shape and specimen surface finish on oxidation of resistant materials. Additionally, the mechanism of steam oxidation was invastigated with the oxygen 18 water. The results show that an increased steam flow rate not only causes faster oxidation rates but also a change in oxide scale morphology. In case of T23, it triggers formation of micro-layered inner oxide, whereas for T92 it promotes the formation of an outer haematite layer. For austenitic steels, the faster steam flow increases the formation of initially protective oxide scales, but also accelerates the growth of oxide nodules with prolonged exposure times. The analysis of the different surface finishes show that clearly the change of the surface finish from ground to polish and pickled (as received) accelerates the oxidation process for austenitic steels, the ground specimens show the slowest oxidation, whereas the pickled specimens oxidise much faster and form thicker scales. Finally, the study of oxidation mechanism show that steam oxidation is not only controlled by the inner diffusion of the oxygen ions but the diffusion of the hydroxides have a significant impact on oxides formation. The results of the study suggest that the hydroxide ions influence formation of the inner oxides.